2016
DOI: 10.21836/pem20160407
|View full text |Cite
|
Sign up to set email alerts
|

Detection of intraocular leptospiral DNA, antibodies and Leptospira spp. in horses with equine recurrent uveitis in different laboratories

Abstract: Summary: Equine recurrent uveitis (ERU) is an ocular disease characterized mainly by recurrent episodes of inflammation, alternating with quiescent episodes of various durations. There are numerous aetiological theories for the cause of ERU, but to date, the "classic ERU" is most commonly associated with an intraocular leptospiral infection. The pars plana vitrectomy has, so far, been the most promising treatment of ERU and is thought to be more successful in eyes with detectable leptospiral antibodies in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 48 publications
1
22
0
6
Order By: Relevance
“…In 14 % of the vitreous specimens of horses with suspected leptospiral uveitis by ophthalmological examination leptospiral antibodies could not be detected neither with MAT nor ELI-SA. This observation is consistent with studies of other authors who also failed to detect specific antibodies in all of the intraocular samples from horses suffering from recurrent uveitis (Wollanke et al 1998a,b, Wollanke et al 2001a,b, Wollanke et al 2004a, Brandes et al 2007, Tömördy et al 2010, Wiehen 2012, Kulbrock et al 2013, Baake et al 2016, Dorrego Keiter et al 2016, Dorrego Keiter et al 2017. The different percentages of Leptospira positive and negative samples might be attributable to different methods in case selection and sampling techniques.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…In 14 % of the vitreous specimens of horses with suspected leptospiral uveitis by ophthalmological examination leptospiral antibodies could not be detected neither with MAT nor ELI-SA. This observation is consistent with studies of other authors who also failed to detect specific antibodies in all of the intraocular samples from horses suffering from recurrent uveitis (Wollanke et al 1998a,b, Wollanke et al 2001a,b, Wollanke et al 2004a, Brandes et al 2007, Tömördy et al 2010, Wiehen 2012, Kulbrock et al 2013, Baake et al 2016, Dorrego Keiter et al 2016, Dorrego Keiter et al 2017. The different percentages of Leptospira positive and negative samples might be attributable to different methods in case selection and sampling techniques.…”
supporting
confidence: 89%
“…Leptospiral DNA could be detected in 61% of the vitreous samples from horses with ERU, whereas in the control group none showed a positive reaction. Other authors reported on 57 % to 100 % of positive test results in intraocular samples from horses with ERU (Faber et al 2000, Wollanke 2002, Gesell 2004, Wollanke et al 2004a, Brandes et al 2007, Wiehen 2012, Baake et al 2016, Dorrego Keiter et al 2016, Schinagl 2017. The frequent detection of leptospiral DNA in intraocular material of equine eyes with recurrent uveitis confirmed that leptospires play a decisive role in the aetiology and pathogenesis of the disease.…”
mentioning
confidence: 98%
“…For some inexplicable reason, recently the calculation of the Goldmann-Witmer coefficient had been revisited as a precondition for the diagnosis of a leptospira-induced uveitis (Gilger 2018, Malalana 2018 as it had been advocated in human ophthalmology for diagnosis of infectious uveitis (Rothova et al 2008). However, an intraocular antibody production in equids had been proved in earlier studies (Wollanke 2002, Wollanke et al 2004) and in addition, PCR and culture results are positive in high percentages , Wollanke et al 2000, Wollanke and Gerhards 2001a, 2001b, Wollanke 2002, Hartskeerl et al 2004, Roczek 2008, Von Borstel et al 2010, Popp et al 2013, Baake et al 2016) and there is ultrastructural evidence of leptospires inside the vitreous of ERU eyes (Niedermaier et al 2006, Brandes et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Detection of antibodies directed against leptospires (Gsell et al 1946, Wood andDavis 1950) and leptospiral DNA in intraocular fluids is not new, but varies considerably between different investigations (Wollanke et al 1998b, Faber et al 2000, Wollanke et al 2001b, Wollanke 2002, Gesell et al 2005, Gilger et al 2008, Loibl 2009, Von Borstel et al 2010, Wiehen 2012, Polle et al 2014, Roth et al 2014, Baake et al 2016, Dorrego-Keiter et al 2016, 2017, Malalana et al 2017. Reasons for this might be the time of sampling (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Die Operation, Vor-und Nachsorge der ERU-Patienten erfolgte, wie bereits beschrieben (Frühauf et al 1998, von Borstel 2005,Tóth et al 2006, 2010 Auch die suprachoroidale Applikation eines Ciclosporin AImplantats (Gilger et al 2000a, Gilger et al 2000b, Gilger et al 2001, Gilger and Spiess 2006 kann aus Sicht der Autoren bei ERU nicht an die Erfolgsrate der PPV anknüpfen, so dass aufgrund mangelnder therapeutischer Alternativen, einer nach wie vor ungeklärten Ätiopa-thogenese der ERU, regionaler Unterschiede in der Leptospirenprävalenz und der Varianz der MAT-Ergebnisse (Baake et al 2016) …”
unclassified